Karol Brzozowski’s Poem about “Our Land” - Ożóg-Winiarska, Zofia (Respectus Philologicus, 2015)
This paper endeavours to renew the scientific description of Karol Brzozowski’s poem entitled Noc strzelców w Anatolii (The Night of Shooters in Anatolia) (1856), which was unjustly forgotten by literary critics, editors, and literary canons. The poem was inspired by the literary masterpieces of Polish romanticism, such as Adam Mickiewicz’s Pan Tadeusz (Mr. Tadeusz)(1834) and Wincenty Pol’s Pieśń o ziemi naszej (A Song of Our Land) (1843). This article reveals the aesthetic, poetic, and narrative qualities of the poem, the elements that constitute its beauty and novelty, particularly with regard to a poetic tale and description where it is possible to discern the elements of romantic improvisation, visual and linguistic disharmonies of expressionist character. The Brzozowski’s poem presents a symbolic expanse of the homeland, which consists of the full lushness of the flora, fauna, natural phenomena, the images of home, fields and forests as well as the landscapes of historical regions of Poland around Warsaw and the borderlands of Southwest Lithuania. This expanse is filled with inner landscapes of an archetype character, remembered and recorded through the senses and emotions in the subconscious of the author and the characters of the poem. These artistic and ideological features are seen as a presage of the future neo-romanticism.